2001
DOI: 10.1182/blood.v97.1.227
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of E2F-1 leads to cytokine-independent proliferation and survival in the hematopoietic cell line BaF-B03

Abstract: Cytokine receptors activate signals that regulate the transcription factor E2F-1, which then coordinates the expression of genes essential for DNA synthesis and cell cycle progression. Overexpression of E2F-1 most often induces S-phase entry followed by apoptosis, but in some cell types it leads to continuous proliferation and transformation. Here, it is shown that constitutive expression of E2F-1 promotes cytokine-independent proliferation in the murine pro-B cell line BaF-B03. There was no enhancement of apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 50 publications
(56 reference statements)
1
25
0
Order By: Relevance
“…We also identified a guanine nucleotide exchange factor that is considered to be one of the activators of Ras signaling pathways through activation of GTP-bound state of Ras superfamily proteins. 65 Interestingly, this study also identified an EST transcript (FB248) with domain in receptor targeting proteins Lin-2 and Lin-7 (L27), guanylate kinase homologs (GuKc), domain present in PSD-95, ETS2, 38 and E2F1 29,30 Cell cycle regulator: WEE1, 39,40 RCC1, 41 …”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We also identified a guanine nucleotide exchange factor that is considered to be one of the activators of Ras signaling pathways through activation of GTP-bound state of Ras superfamily proteins. 65 Interestingly, this study also identified an EST transcript (FB248) with domain in receptor targeting proteins Lin-2 and Lin-7 (L27), guanylate kinase homologs (GuKc), domain present in PSD-95, ETS2, 38 and E2F1 29,30 Cell cycle regulator: WEE1, 39,40 RCC1, 41 …”
Section: Discussionmentioning
confidence: 76%
“…28 The significance of E2F1 in cycling status of human hematopoietic cells has also been demonstrated. 29,30 Since FB-HSPCs differ from MPB-HSPCs based on cell cycle status, we examined expression of E2F1 in FB-HSPCs versus MPB-HSPCs. E2F1 was found to be more highly expressed in FB-HSPCs than MPB-HSPCs ( Figure 3D top) using semiquantitative PCR.…”
Section: Org Frommentioning
confidence: 99%
“…Some transcription factors such as ATFx seem to have purely antiapoptotic activities (Persengiev et al, 2002). E2F-1 has both activities as it is required for T-cell apoptosis in vivo and its overexpression induces apoptosis in a number of cell lines but inhibits apoptosis in others such as Baf-3 cells (Field et al, 1996;Gala et al, 2001). However, increased activity of many transcription factors such as c-Jun, c-Fos, E2F-1, p75 c-Myb, FKH-L1, c-Myc and p53 induces apoptosis or sensitises the cells to proapoptotic stimuli (Harrington et al, 1994;Qin et al, 1994;Lassus et al, 1996;Preston et al, 1996;Bossy-Wetzel et al, 1997;Dijkers et al, 2000;Kumar et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of E2F1 was shown to promote leukemia cell proliferation in a cytokine independent manner, and a variety of cell cycle dependant cyclins were maintained by E2F1 without cytokine stimulation [39]. On the other hand, E2F1 induces cell apoptosis through cooperating with either p53 [40] or p73 [41].…”
Section: Discussionmentioning
confidence: 99%